(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
A bedridden condition with long-term bed rest often results in a pressure ulcer or decubitus, primarily in protruding body parts. Aiming at minimizing the risk and preventing the development of an advanced grade decubitus, an innovative smart pressure-reducing mattress was developed and tested in healthy adults to evaluate the rest function, basically. Back to the basic function of a mattress, this study aimed at evaluating the rest function of a smart mattress by analyzing the indicators of relaxation, rest facilitation, and sleep inducement, and their correlation with comfort after 40 minutes of utilization in the supine position. This was an experimental study employing the one-group post-test only design. The sample was 29 female nursing students (n=29). Instruments included a smart pressure-reducing mattress and the rest function questionnaire. Descriptive statistics and the Spearman Rank correlation test were employed in data analysis (α<0.05). The majority gave maximum scores for indicators of relaxed feeling (69%), rest facilitation (69%), sleep inducement (65.5%), and comfort (79.3%). Comfort (M ± SD = 81.03 ± 6.38; 2.79 ± 0.41) was strongly correlated with relax feeling (M ± SD = 3.69 ± 0.47) and rest facilitation (M ± SD = 3.66 ± 0.55) [p<0.05; ρ=0.523 and ρ=0.662, respectively]. Although most respondents fell asleep after 40 minutes lying down on the smart mattress, comfort was not correlated with sleep inducement (M ± SD = 3,52 ± 0,78; p=0.290). The rest function of the smart mattress is working very well. Utilizing a smart mattress for 40 minutes in supine position can promote comfortable rest by improving relax feeling and facilitating rest in healthy adults. There is a need for a future randomized controlled trial (RCT), testing this smart mattress directly against a regular mattress.